13C NMR of glutamate for monitoring the pentose phosphate pathway in myocardium. (26th April 2021) - Jin, Eunsook S.; Lee, Min H.; Malloy, Craig R.
Abstract : After administration of 13 C‐labeled glucose, the activity of the pentose phosphate pathway (PPP) is often assessed by the distribution of 13 C in lactate. However, in some tissues, such as the well‐oxygenated heart, the concentration of lactate may be too low for convenient analysis by NMR. Here, we examined 13 C‐labeled glutamate as an alternative biomarker of the PPP in the heart. Isolated rat hearts were perfused with media containing [2, 3‐ 13 C2 ]glucose and the tissue extracts were analyzed. Metabolism of [2, 3‐ 13 C2 ]glucose yields [1, 2‐ 13 C2 ]pyruvate via glycolysis and [2, 3‐ 13 C2 ]pyruvate via the PPP. Pyruvate is in exchange with lactate or is further metabolized to glutamate through pyruvate dehydrogenase and the TCA cycle. A doublet from [4, 5‐ 13 C2 ]glutamate, indicating flux through the PPP, was readily detected in 13 C NMR of heart extracts even when the corresponding doublet from [2, 3‐ 13 C2 ]lactate was minimal. Benfotiamine, known to induce the PPP, caused an increase in production of [4, 5‐ 13 C2 ]glutamate. In rats receiving [2, 3‐ 13 C2 ]glucose, brain extracts showed well‐resolved signals from both [2, 3‐ 13 C2 ]lactate and [4, 5‐ 13 C2 ]glutamate in 13 C NMR spectra. Assessment of the PPP in the brain based on glutamate had a strong linear correlation with lactate‐based assessment. In summary, 13 C NMR analysis of glutamate enabled detection of the low PPP activity in isolated hearts. This analyte is an alternative to lactate for monitoring the PPP with the use of [2, 3‐ 13 C2 ]glucose. Abstract : It is a challenge to assess the pentose phosphate pathway (PPP) in the heart with 13 C NMR analysis of lactate. We examined 13 C‐labeled glutamate as an alternative biomarker of the PPP in the heart supplied with [2, 3‐ 13 C2 ]glucose. A doublet from [4, 5‐ 13 C2 ]glutamate, indicating flux through the PPP, was readily detected in 13 C NMR of heart extracts even when the corresponding doublet from [2, 3‐ 13 C2 ]lactate was minimal. 13 C NMR analysis of glutamate enabled detection of the low PPP activity in isolated hearts.